Membrane technology: historical development (2019)
Membrane Technology allows to separate materials of different molecular weight, and that is why this technology has been very important through history, reducing energy cost and preserving natural resources. Nowadays it has a lot of applications such as obtaining whey proteins, desalination of seawater and wastewater cleanup, obtaining volatile components from soluble coffee, among others. In this review a description of Membrane Technology development and its critical applications is introduced.